Función exponencial: análisis del trabajo matemático de estudiantes de humanidades - Vivas Pachas, Jorge Luis (2022)
The research report, which is a summary of the first author's master's thesis, aims to analyze the mathematical work of students in humanities majors when they solve a task on the topic of exponential function. For this purpose,we are based on the theory of the Mathematical Workspace (MWS) and we use the MWS method for the analysis. The research was carried out with students of the first cycle of humanities careers (16 and 18 years old) of a private university in Lima-Peru, in which a task of the exponential function topic was elaborated. Based on the analysis of the mathematical actions, the activation of the semiotic, instrumental and discursive genesis is evidenced, being the semiotic and discursive genesis the most frequent. Likewise, the activation of two vertical planes, the semiotic-discursive and the instrumental-discursive of the ETM, is evidenced